Penguatan Kapasitas BUMDes dan Prakarsa BUMDesma di Kecamatan Ambarawa Kabupaten Pringsewu - Fahmi, Teuku; Yulianto (UNIB Press, 2024)
The initiative to establish joint village-owned enterprises (BUMDesma), as local-scale village businesses run by BUMDes, has become increasingly common since the enactment of Law Number 6 of 2014 on Villages. Developing these joint BUMDes is also a strategic policy of the current